Are There Financial Sacrifices in Ethical Investing? A Comparative Study of Indonesia and Malaysia - Amalia, Farah; Ismail, Shafinar; Fauzi, Muchamad; Mohd Nor, Amirudin (Journal of Indonesian Economy and Business, 2025)
Introduction/Main Objectives: Ethical investment in Southeast Asia is gaining traction, particularly in countries like Indonesia and Malaysia. This research aims to measure the performance of ethical investments and compare them with their opposite category, sin stocks. Investors should avoid sin stocks because they operate in controversial areas and go against ethical investment principles. Background Problems: Previous research conducted in developed countries shows that ethical investments are inferior to sin stocks, thus investors suffer financial sacrifices. Novelty: A comprehensive ethical investment instrument that involves sustainability and religion-based investments. Formation of sin stock portfolios in two Muslim countries. Research Methods: A volatility analysis and a descriptive analysis were carried out to provide a comprehensive picture of the performance of ethical and sin stocks. The analysis continues by comparing and explaining why and how the results occurred. Finding/Results: Ethical stock returns underperformed sin stocks in Malaysia, and ethical stocks outperformed sin stocks in Indonesia. This exciting result can be explained by the differences in screening criteria, perceptions, and regulations in these two neighboring countries. Conclusion: There are no financial sacrifices in ethical investing in Indonesia, so ethical investors do not need to hesitate. They are advised to invest ethically because they achieve two goals at once. Meanwhile, Malaysian ethical investors must be prudent and careful in investing to continue achieving social goals and mitigating losses.